Co-production of activated carbon, fuel-gas, and oil from the pyrolysis of corncob mixtures with wet and dried sewage sludge. Issue 6 (June 2014) - Shao, Linlin; Jiang, Wenbo; Feng, Li; Zhang, Liqiu
This study explored the amount and composition of pyrolysis gas and oil derived from wet material or dried material during the preparation of sludge-corncob activated carbon, and evaluated the physicochemical and surface properties of the obtained two types of sludge-corncob-activated carbons. For wet material, owing to the presence of water, the yields of sludge-corncob activated carbon and the oil fraction slightly decreased while the yield of gases increased. The main pyrolysis gas compounds were H2 and CO2, and more H2 was released from wet material than dried material, whereas the opposite holds for CO2 . Heterocyclics, nitriles, organic acids, and steroids were the major components of pyrolysis oil. Furthermore, the presence of water in wet material reduced the yield of polycyclic aromatic hydrocarbons from 6.76% to 5.43%. The yield of furfural, one of heterocyclics, increased sharply from 3.51% to 21.4%, which could be explained by the enhanced hydrolysis of corncob. In addition, the surface or chemical properties of the two sludge-corncob activated carbons were almost not affected by the moisture content of the raw material, although their mesopore volume and diameter were different. In addition, the adsorption capacities of the two sludge-corncob activated carbons towards Pb and nitrobenzene were nearly identical.